Facility Layout Design of New Warehouse and Implementation of Multi-Criteria Decision Making for Product Allocation at PT XYZ - Viter Pranata; Santoso Santoso (OPSI, 2022)
As the company's business grows, there product distribution network will increase. This will cause distribution costs to be increase. Therefore, the company decided to build a new warehouse in order to increase the efficiency of distribution costs. This new warehouse will use two storage systems, those are racking system and floor storage, so it need to design a good layout so that the space provided can be used effectively and efficiently. A dedicated storage policy is used to make workers easier to find products so that the time of product retrieval is faster. Another thing to consider is the proper allocation of products because this can affect the total distance of product movement which can also affect the time of product retrieval. In this study, multi-criteria decision making (MCDM) will be used to determine which product will be the main priority to be placed near the inbound/outbound (I/O). Furthermore, we will consider supporting facilities so that warehousing activities can run well where the preparation of each facility will use the activity relationship chart (ARC).